Grass planting brick based on phosphogypsum-based composite cementing material and preparation method of grass planting brick

By combining modified phosphogypsum powder with blast furnace slag powder in grass planting bricks, the problems of phosphogypsum storage and environmental pollution are solved, the utilization rate of phosphogypsum and the performance of phosphogypsum are improved, and the cost reduction and environmental friendliness are achieved. Road components preparation.

CN119191804APending Publication Date: 2024-12-27WUHAN UNIV OF TECH +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411235238.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

When phosphogypsum is used as the raw material for road components in the prior art, the release of phosphorus and fluorine is prone to cause environmental pollution, and the traditional materials are costly, which limits its wide application.

Method used

Using grass-planting bricks based on phosphogypsum-based composite gelling material, the modified phosphogypsum powder is mixed with blast furnace slag powder by calcining and ball milling, and adding retarder, waterproofing agent and aggregate to prepare high-quality Grass-planted bricks with strength and durability reduce the stock of phosphogypsum piles and improve their utilization rate.

Benefits of technology

It effectively reduces the risk of pollution from phosphogypsum to the environment, improves the utilization rate of phosphogypsum and the performance of grass-planting bricks, reduces production costs, and meets the safety, aesthetics and environmentally friendly requirements of road components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119191804A_ABST
    Figure CN119191804A_ABST
Patent Text Reader

Abstract

The invention relates to a grass planting brick based on an ardealite-based composite cementing material and a preparation method thereof.The grass planting brick is prepared from, by mass, 100 parts of the ardealite-based composite cementing material, 0.05-0.3 part of a retarder, 0-0.5 part of a waterproof agent, 0-70 parts of aggregate and 40-70 parts of water, and the ardealite-based composite cementing material is prepared from 70-90 parts of modified ardealite powder, 10-30 parts of blast furnace slag powder and 0-3.5 parts of an alkaline activator; the modified ardealite powder is obtained by calcining and ball-milling ardealite powder. According to the invention, the stockpiling amount of the phosphogypsum can be effectively reduced, the utilization rate of the phosphogypsum is improved, and the modified phosphogypsum powder is calcined and ball-milled, so that leaching of heavy metals and harmful chemical substances can be effectively avoided, and the influence of soluble phosphorus and fluorine is reduced; the preparation method is simple and low in cost, the utilization rate of the ardealite raw material can be increased, and the obtained grass planting brick can meet related standard requirements.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of road bricks and stones, and in particular to a grass-planting brick based on a phosphogypsum-based composite cementitious material and a preparation method thereof. Background Art

[0002] When phosphoric acid is produced by the wet process, phosphogypsum is a byproduct, with 4-5 tons of phosphogypsum produced for every ton of phosphoric acid produced. Currently, phosphogypsum is usually stored in open-air piles, but since it contains impurities such as free phosphoric acid and fluoride, large-scale storage may cause environmental pollution.

[0003] In the current construction of transportation infrastructure, the preparation and application of road components such as curbstones, slope protection bricks, permeable bricks, and grass bricks are of great significance to ensure road safety, beauty, and environmental friendliness. These components are currently mainly made of ordinary concrete, which is favored for its high strength and long life. However, due to the high cost of its raw materials, its promotion and application in a wider range is limited to a certain extent.

[0004] In recent years, with the continuous increase of industrial solid waste, how to effectively utilize these wastes has become an important research topic. Researchers have begun to explore the use of recycled aggregates such as construction waste to replace traditional natural aggregates to prepare road components. This method can not only reduce production costs, but also promote the recycling of construction waste and reduce the burden on the environment. In addition, as an industrial by-product, phosphogypsum is produced in large quantities, and its treatment and utilization have also become an urgent problem to be solved. Using phosphogypsum as a resource-utilized material for the preparation of road components can not only reduce its potential impact on the environment, but also increase its economic value. However, phosphogypsum contains a large amount of soluble phosphorus. If it is not handled properly, it may cause pollution to the environment. Therefore, while utilizing phosphogypsum as a resource, it is also necessary to pay attention to the release of phosphorus, fluorine, etc. Summary of the invention

[0005] The purpose of the present invention is to overcome the above-mentioned technical deficiencies, provide a grass-planting brick based on phosphogypsum-based composite cementitious material and a preparation method thereof, and solve the technical problem in the prior art that when phosphogypsum is used as a raw material for road components, the release of elements such as phosphorus and fluorine can easily cause environmental pollution.

[0006] In order to achieve the above technical purpose, the technical solution provided by the present invention is: In a first aspect, the present invention provides a grass-planting brick based on a phosphogypsum-based composite cementitious material, wherein the raw materials include, by mass, 100 parts of phosphogypsum-based composite cementitious material, 0.05-0.3 parts of a retarder, 0-0.5 parts of a waterproofing agent, 0-70 parts of an aggregate and 40-70 parts of water, wherein the phosphogypsum-based composite cementitious material includes 70-90 parts of modified phosphogypsum powder, 10-30 parts of blast furnace slag powder and 0-3.5 parts of an alkaline activator; the modified phosphogypsum powder is obtained by calcining and ball milling the phosphogypsum powder.

[0007] In a second aspect, the present invention provides a method for preparing grass bricks based on a phosphogypsum-based composite cementitious material, comprising the following steps: calcining phosphogypsum powder to obtain calcined phosphogypsum powder, and ball-milling the calcined phosphogypsum powder to obtain modified phosphogypsum powder; mixing the modified phosphogypsum powder, blast furnace slag powder and an alkaline activator to obtain a phosphogypsum-based composite cementitious material; mixing the phosphogypsum-based composite cementitious material, a retarder, a waterproofing agent, aggregate and water to obtain gypsum mortar; pouring the gypsum mortar into a mold, curing and forming it, and obtaining grass bricks based on a phosphogypsum-based composite cementitious material.

[0008] Compared with the prior art, the beneficial effects of the present invention include: The present invention utilizes a small amount of blast furnace slag powder and modified phosphogypsum powder to prepare a phosphogypsum-based composite cementitious material, which can effectively reduce the stockpile of phosphogypsum and improve its utilization rate. The modified phosphogypsum powder can be calcined and ball-milled to effectively avoid the leaching of heavy metals and harmful chemicals and reduce the influence of soluble phosphorus and fluorine. The alkaline activator can fully stimulate the hydration activity of the modified phosphogypsum powder and blast furnace slag powder, which is beneficial to improving the strength of the grass bricks finally obtained. The retarder is used to prolong the gel time of the mortar without affecting the strength of the final product. The utilization rate of the phosphogypsum raw material is regulated by controlling the amount of aggregate. The waterproofing agent is used to improve the water resistance of the grass bricks, and can improve the frost resistance and durability of the grass bricks obtained by combining with other raw materials of the present invention. The preparation method of the present invention is simple and low in cost, and can improve the utilization rate of the phosphogypsum raw materials. The obtained grass bricks can meet the requirements of relevant standards. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 The 28-day bending and compressive strength of the grass-planting brick specimens obtained in Examples 1-3 of the present invention; Figure 2 is the result of the mass loss rate in the dry-wet cycle test of the present invention; Figure 3 is the change in compressive strength in the dry-wet cycle test of the present invention; Figure 4 is the result of the mass loss rate in the freeze-thaw cycle test of the present invention; Figure 5 It is the result of the compressive strength loss rate in the freeze-thaw cycle test of the present invention. DETAILED DESCRIPTION

[0010] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0011] In the process of developing phosphogypsum as a raw material for the production of road components, environmental protection and safety are the primary concerns during the design and implementation stages. This requires effective preventive measures to prevent harmful chemicals such as water-soluble phosphorus pentoxide and fluorine from being released from the material during long-term use, thereby avoiding damage to the surrounding ecological environment. In addition to environmental safety, the formulation of the material and the selection of manufacturing technology are also crucial links, which involve in-depth research on different material combinations, including the ratio of aggregates and additives, as well as fine-tuning of the production process to ensure that road components can meet the expected standards in terms of mechanical strength, durability, and adaptability to various climatic conditions. The long-term performance and service life of road components are directly affected by these factors.

[0012] Therefore, while pursuing the improvement of the efficiency of phosphogypsum use, it is crucial to maintain or improve the comprehensive performance of the material. This not only involves the efficient use of resources, but also includes improving the overall quality of road components and extending their service life. On this basis, the present invention provides a grass-planting brick based on a phosphogypsum-based composite cementitious material and a preparation method thereof. The obtained grass-planting brick can provide performance comparable to or even better than traditional materials while ensuring environmental safety, opening up new possibilities for the construction and maintenance of transportation infrastructure.

[0013] In a first aspect, the present invention provides a grass-planting brick based on a phosphogypsum-based composite cementitious material, wherein the raw materials include, by weight, 100 parts of the phosphogypsum-based composite cementitious material, 0.05 to 0.3 parts of a retarder, 0 to 0.5 parts of a waterproofing agent, 0 to 70 parts of an aggregate, and 40 to 70 parts of water. The phosphogypsum-based composite cementitious material includes 70-90 parts of modified phosphogypsum powder, 10-30 parts of blast furnace slag powder and 0-3.5 parts of alkaline activator; the modified phosphogypsum powder is obtained by calcining and ball milling the phosphogypsum powder.

[0014] In the present invention, a small amount of blast furnace slag powder is mixed with modified phosphogypsum powder to prepare a phosphogypsum-based composite cementitious material, which can effectively reduce the stockpile of phosphogypsum, improve its utilization rate, and is green and environmentally friendly.

[0015] Preferably, the alkaline activator includes calcium hydroxide. The present invention can change the hydration environment of the phosphogypsum-based composite cementitious material by adding a small amount of calcium hydroxide reagent to the phosphogypsum-based composite cementitious material, so that it can be hydrated under alkaline conditions, which can meet the required alkaline environment, and fully stimulate the hydration activity of the modified phosphogypsum powder and slag powder, so that the prepared composite cementitious material specimen exhibits better compressive and flexural strength.

[0016] Further preferably, in the present invention, 3% calcium hydroxide is added as an alkaline activator relative to the total mass of the modified phosphogypsum powder and the blast furnace slag powder, which can effectively stimulate the gelling activity of the phosphogypsum-based composite cementitious material.

[0017] Preferably, the retarder includes a plant protein retarder. The present invention uses a plant protein retarder as one of the admixtures, which can effectively prolong the setting time of the gypsum mortar, and has little effect on the strength of the obtained grass bricks, and has the advantages of being green, environmentally friendly and convenient for construction; the present invention uses a plant protein retarder, which helps to improve the workability of the gypsum mortar and the quality of the final product.

[0018] Preferably, the waterproofing agent includes sodium methyl silicate; the working principle of sodium methyl silicate is to react with water and CO2 to form a waterproof resin film on the surface of the crystal, which prevents water molecules from corroding from the outside to the inside of the gypsum hardened body, thereby enhancing the water resistance of the gypsum-based grass bricks, and by combining with other raw materials of the present invention, the frost resistance and durability of the obtained grass bricks can be improved.

[0019] Preferably, the aggregate includes coarse aggregate and fine aggregate in a mass ratio of (1.2-1.5):1, the particle size of the coarse aggregate is 4.75-26.5 mm, the particle size of the fine aggregate is below 4.75 mm, and the particle gradation of the coarse aggregate and the fine aggregate is a continuous gradation.

[0020] More preferably, the coarse aggregate is limestone aggregate, and the fine aggregate is river sand; or both the coarse aggregate and the fine aggregate are recycled aggregate, and the recycled aggregate is obtained by granulating modified phosphogypsum powder and water.

[0021] Further preferably, the particle gradation of the coarse aggregate is: 16 mm to 26.5 mm accounts for 30%, and 4.75 mm to 16 mm accounts for 70%; the particle gradation of the fine aggregate meets the continuous gradation of natural sand zone II.

[0022] Preferably, the fineness of the modified phosphogypsum powder is 80-200 mesh; and the blast furnace slag powder is S95 grade slag.

[0023] Preferably, the water-to-solid ratio is 0.3-0.4, wherein the water-to-solid ratio refers to the mass ratio of water to solid powder. The present invention takes into account the main factors affecting the performance of concrete, including the amount of cementitious materials, gradation, water consumption and admixtures, etc. During the trial mixing process, if the water consumption is too low, the obtained mortar slurry has the problem of too low fluidity and difficulty in forming, so the present invention needs to control the amount of water.

[0024] In a second aspect, the present invention provides a method for preparing grass-planting bricks based on phosphogypsum-based composite cementitious materials, comprising the following steps: The phosphogypsum powder is calcined to obtain calcined phosphogypsum powder, and the calcined phosphogypsum powder is ball-milled to obtain modified phosphogypsum powder; The modified phosphogypsum powder, blast furnace slag powder and alkaline activator are mixed to obtain a phosphogypsum-based composite cementitious material; The phosphogypsum-based composite cementitious material, the retarder and the aggregate are mixed to obtain a powder mixture, the waterproofing agent and water are mixed to obtain a liquid mixture, and the powder mixture and the liquid mixture are mixed evenly to obtain a gypsum mortar; The gypsum mortar is poured into a mold, cured and formed, and a grass-planting brick based on the phosphogypsum-based composite cementitious material is obtained.

[0025] Preferably, the calcination temperature is 200° C. to 300° C., and the calcination time is 10 to 20 min.

[0026] Preferably, the particle size of the calcined phosphogypsum powder is less than 74 μm.

[0027] Preferably, the calcined phosphogypsum powder is ball-milled for 3 to 5 minutes to obtain the modified phosphogypsum powder.

[0028] Preferably, the aggregate is soaked in water before being mixed.

[0029] The present invention is further described in detail below through specific examples. To avoid redundant description, the main raw materials and preparation conditions used are described as follows: (1) Calcined phosphogypsum powder Ordinary phosphogypsum powder that has not been properly treated contains a variety of harmful substances, including heavy metals and harmful chemicals. If it is used directly in production or construction, there is a potential risk of causing pollution to the surrounding soil and water. In the present invention, the phosphogypsum powder is provided by Wuhan Juhai Environmental Technology Co., Ltd., Hubei Province, and is a gray powder. The phosphogypsum is sent to the dryer through a raw material conveyor to remove free water, and the free water content of the material at the dryer outlet is controlled to be less than 5%. The material temperature is controlled at 240°C during calcination. oC, calcination time is 15 min. The particle size of calcined phosphogypsum powder is less than 74 μm. According to the "Chemical Analysis Method for Gypsum" (GB / T 5484-2012), calcium sulfate hemihydrate accounts for 61.48% in the calcined phosphogypsum. The chemical composition of calcined phosphogypsum based on XRF analysis is shown in Table 1 below.

[0030] Table 1 Chemical composition of calcined phosphogypsum based on XRF analysis

[0031] (2) Phosphogypsum-based composite cementitious materials The calcined phosphogypsum material after calcination is sent to the ball milling system. The ball milling time is about 4 minutes to obtain modified phosphogypsum powder with a fineness of 80-200 mesh.

[0032] The modified phosphogypsum powder, granulated blast furnace slag powder and alkaline activator were mixed evenly in a mass ratio of 70:30:3 to obtain a phosphogypsum-based composite cementitious material. The granulated blast furnace slag powder was S95 grade slag with a specific surface area of ​​600 m 2 / kg. Table 2 is the main chemical composition of blast furnace slag powder based on XRF analysis.

[0033] Table 2 Main chemical components of blast furnace slag powder based on XRF analysis

[0034] Among them, the alkaline activator is selected as Ca(OH)2, which is an analytically pure chemical reagent from Shanghai Xilong Chemical Company. The technical conditions meet the standards and the Ca(OH)2 content is greater than 95%.

[0035] (3) Additives The retarder of the present invention is a plant protein retarder from Beijing Longtengda Chemical Industry.

[0036] The waterproofing agent used is sodium methyl silicate waterproofing agent, a colorless liquid produced by Hangzhou Baonuo Chemical Co., Ltd., and all technical conditions of admixtures meet the standards.

[0037] (4) Natural aggregates The coarse aggregate used in the present invention is limestone aggregate with a diameter of 4.75-26.5 mm and an apparent density of 2.82 g / cm 3 , bulk density 1.43 g / cm 3, mud content 0.75%, crushing index 5%, its various indicators can meet the various index requirements in "Construction Pebbles and Crushed Stones" (GB / T 14685-2011), and fully meet the test requirements. The test used single particle gradings of 4.75 mm~16 mm and 16 mm~26.5 mm to mix and prepare a continuous graded crushed stone with a particle size of 4.75~26.5 mm. The grading data are shown in Table 3.

[0038] Table 3 Crushed stone gradation data

[0039] The fine aggregate is river sand with a fineness modulus of 2.7 and an apparent density of 2.63 g / cm 3 , bulk density 1.48 g / cm 3 Its various indicators can meet the requirements of "Construction Sand" (GB / T 14684-2011), the particle gradation meets the continuous gradation of natural sand zone II, it is air-dried and dehydrated before use, and the moisture content can be ignored. The screening results of fine aggregate are shown in Table 4.

[0040] Table 4 Fine aggregate screening results

[0041] (5) Recycled aggregate The present invention uses recycled aggregate provided by Hubei Juhai Environmental Technology Co., Ltd., which is prepared by mixing phosphogypsum powder and water and then granulating. Basic performance tests were conducted on the continuously graded recycled aggregate, and the test results are shown in Table 5. The test process was carried out in accordance with the "Highway Engineering Aggregate Test Code" (JTG E42-2005).

[0042] Table 5 Basic properties of recycled aggregate

[0043] Example 1 (Preparation of components using phosphogypsum-based composite cementitious materials) In this embodiment, gypsum mortar is prepared by using phosphogypsum-based composite cementitious material slurry, including the following steps: The phosphogypsum-based composite cementitious material and the retarder are first dry-mixed, and then water is gradually added and stirred for a total time of no more than 6 minutes to obtain gypsum mortar; wherein, the phosphogypsum-based composite cementitious material includes 70 parts of modified phosphogypsum powder, 30 parts of blast furnace slag powder and 3 parts of alkaline activator, and the mixing ratio is shown in Table 6.

[0044] Table 6 Raw material ratio of Example 1

[0045] The amount of retarder used is relative to the total mass of the phosphogypsum-based composite cementitious material.

[0046] Example 2 (Preparation of components by mixing phosphogypsum-based composite cementitious materials with natural aggregates) The difference from Example 1 is that natural aggregate is added; the specific preparation steps of the gypsum mortar in this embodiment include: The phosphogypsum-based composite cementitious material (same as in Example 1), retarder and natural aggregate are first dry-mixed, and then water is gradually added and stirred for a total time of no more than 6 minutes to obtain gypsum mortar; wherein the mass ratio of the phosphogypsum-based composite cementitious material to the natural aggregate is 6:4, and the specific mix ratio is shown in Table 7.

[0047] Table 7 Raw material ratio of Example 2

[0048] It should be emphasized that in the preparation process of this embodiment, the aggregate was soaked in advance. This is because the apparent open pores of the aggregate have a certain amount of water absorption. The aggregate was tested after soaking in water, and mixed after adsorbing the free water on the surface of the aggregate according to the apparent density test method. Calculations show that the water-solid ratio of this embodiment (that is, the total water consumption divided by the total amount of aggregate and cementitious material) is 0.31, which is the optimal water consumption under this mix ratio. Finally, a good mixing effect was obtained, and the resulting gypsum mortar has good fluidity and is conducive to molding.

[0049] Example 3 (Preparation of components by mixing phosphogypsum-based composite cementitious materials with phosphogypsum recycled aggregate) The only difference from Example 2 is that natural aggregate is replaced by recycled aggregate, and the amount of water is adjusted adaptively, and the other steps and conditions are the same as Example 2. The specific differences include: The phosphogypsum powder is mixed with water to form a granular recycled aggregate, which is then screened. Referring to the continuous particle size of the natural aggregate in Example 2, the recycled aggregate is weighed and mixed according to the corresponding proportion on each layer of the sieve to ensure that the particle size of Example 3 is consistent with that of Example 2.

[0050] Considering that the water absorption of phosphogypsum recycled aggregate is strong, exceeding 25%, the method of pre-immersing the aggregate is also adopted in the preparation process of Example 3, and the mass ratio of phosphogypsum-based composite cementitious material to recycled aggregate is 6:4, and the water-solid ratio is 0.4.

[0051] Example 4 The only difference from Example 1 is that 0.3% of the waterproofing agent sodium methyl silicate is added (first mixed with water and then mixed with the powder).

[0052] Example 5 The only difference from Example 2 is that 0.3% of the waterproofing agent sodium methyl silicate is added.

[0053] Example 6 The only difference from Example 3 is that 0.3% of the waterproofing agent sodium methyl silicate is added.

[0054] Example 7 The only difference from Example 1 is that 0.5% of the waterproofing agent sodium methyl silicate is added.

[0055] Example 8 The only difference from Example 2 is that 0.5% of the waterproofing agent sodium methyl silicate is added.

[0056] Example 9 The only difference from Example 3 is that 0.5% of the waterproofing agent sodium methyl silicate is added.

[0057] Example 10 The only difference from Example 1 is that 0.7% of the waterproofing agent sodium methyl silicate is added.

[0058] Embodiment 11 The only difference from Example 2 is that 0.7% of the waterproofing agent sodium methyl silicate is added.

[0059] Example 12 The only difference from Example 3 is that 0.7% of the waterproofing agent sodium methyl silicate is added.

[0060] Comparative Example 1 Compared with Example 1, slag powder and Ca(OH)2 were removed and a pure modified phosphogypsum powder hardened body was obtained at a water-binder ratio of 0.5.

[0061] Performance Testing The grass brick specimens were prepared according to the "Test Procedure for Cement and Cement Concrete for Highway Engineering" (JTG 3420-2020). The specific preparation process is as follows: the obtained gypsum mortar was poured into the oiled mold to make a 150×150×150 mm cubic compression specimen and a 100×100×150 mm bending tensile specimen. After compaction, the mold was sealed and cured at room temperature for 24 hours before demolding. The sealed curing was continued until the test age, and the temperature was controlled at 25±2 o C.

[0062] 1. After the specified age, the samples are tested for flexural tensile and compressive strength according to the "Testing Procedures for Cement and Cement Concrete for Highway Engineering" (JTG 3420-2020). Each group of three specimens is tested at 40±2 o C oven to constant weight, using MTS testing machine.

[0063] Tests under the same conditions found that compared with comparative example 1, the flexural strength and compressive strength of the test piece obtained in Example 1 can be increased by about 1 to 2 times, indicating that the addition of slag powder and Ca(OH)2 significantly improved the performance of the phosphogypsum composite material.

[0064] The test pieces obtained in Examples 1-3 of the present invention were tested under the same conditions, and their 28-day flexural strength and compressive strength are shown in Table 8.

[0065] Table 8 Bending strength and compressive strength of the embodiments of the present invention and the comparative examples

[0066] 2. 28-day curing sample after 16 hours 40 o C heating, 2 hours room temperature cooling, 4 hours 20 ± 3 o C water immersion cycle, the quality and strength loss are tested after every 10 cycles. Figure 2 and Figure 3 shown.

[0067] observe Figure 2 and Figure 3 It can be found that the quality of the pure modified phosphogypsum sample of comparative example 1 significantly decreased after experiencing the dry-wet alternation, and its strength was almost lost after completing 20 cycles. In contrast, Examples 1-3, to which slag and alkaline activators were added, all showed a certain resistance to dry-wet alternation damage. After 40 cycles of testing, the strength of the samples of Examples 1-3 decreased by 45%, 35% and 53%, respectively. Among these solutions, the sample of Example 2 showed better durability.

[0068] 3. According to the Standard for Test Methods for Long-term Performance and Durability of Ordinary Concrete (GB / T50082-2019), the antifreeze performance test was carried out by slow freezing method to simulate the actual freeze-thaw environment. After the freezing test, the sample of Example 2 with the strongest mechanical properties had severe peeling on the surface when it experienced the tenth freeze-thaw cycle, and the material showed obvious loss.

[0069] Based on this, in order to improve the water resistance and durability of phosphogypsum-based products, sodium methyl silicate was added as a waterproofing agent on the basis of Examples 1-3. In Examples 4-12, the dosage of sodium methyl silicate was 0.3%, 0.5% and 0.7% respectively relative to the phosphogypsum-based composite cementitious material to study the effect of different dosages on the mechanical properties of the specimens of each embodiment. The results are shown in Table 9.

[0070] Table 9 Effect of different sodium methyl silicate dosages on the mechanical properties of specimens

[0071] It can be observed from Table 9 that when the dosage of the waterproofing agent is less than 1%, the compressive strength of the specimens obtained with the same basic formula (other raw materials are the same except for the waterproofing agent, such as Example 1, Example 4, Example 7 and Example 10) fluctuates very little. Therefore, it is believed that when the dosage of the waterproofing agent does not exceed 1%, it has no significant effect on the mechanical strength of the specimen.

[0072] Two waterproofing agent dosages of 0.3% and 0.5% were selected, and durability tests were conducted on Examples 4-9. After 28 days of curing, the specimens were evaluated for durability through freeze-thaw tests, and the mass loss rate and strength loss rate were recorded every ten cycles. The results are shown in Figure 4 and Figure 5 .

[0073] Figure 4 and Figure 5 The results show that all specimens experienced surface peeling and strength loss during the freeze-thaw cycle, but the loss rate increased significantly after 25 cycles, indicating that the antifreeze performance dropped sharply at this time, but compared with the case without adding waterproofing agent, serious peeling occurred in the 10th freeze-thaw cycle. The addition of waterproofing agent in the present invention effectively improved its antifreeze performance. The specimens of Example 2, which were prepared by mixing phosphogypsum-based composite cementitious materials and natural aggregates, showed better antifreeze durability than other examples. Compared with Example 1, the antifreeze performance was improved by mixing phosphogypsum-based composite cementitious materials with natural aggregates in Example 2; while the high porosity and water absorption of the phosphogypsum recycled aggregate in Example 3 had an adverse effect on its durability.

[0074] 4. In civil engineering applications, it is necessary to ensure that harmful impurities in phosphogypsum do not pollute the environment, especially soluble phosphorus and fluorine. According to the standard "Phosphogypsum" (GB / T 23456-2018), water-soluble P2O5 and F in phosphogypsum - The content of phosphorus and fluorine shall not exceed 0.20% and 0.10% respectively. After testing, the modified phosphogypsum used in the present invention meets these standards, thus eliminating the environmental risks of soluble phosphorus and fluorine.

[0075] Nevertheless, phosphogypsum also contains heavy metals. When used in practice, its leachate must meet the surface water and groundwater quality standards to ensure environmental safety. After the cured specimens were crushed, the leachate was prepared according to the "Solid Waste Leaching Toxicity Leaching Method Horizontal Oscillation Method" (HJ 557-2010), and the element concentration was analyzed by plasma emission spectrometry. Table 10 lists the concentrations of heavy metals in the leachate of the specimens obtained in different embodiments, and compares them with the limit values ​​of the "Groundwater Quality Standard" (GB / T 14848-2017) and the "Surface Water Environmental Quality Standard" (GB 3838-2022).

[0076] Table 10 Leachate test results

[0077] It can be clearly seen from the data in Table 10 that the contents of certain heavy metals in the leachate of the test pieces made of pure phosphogypsum, such as lead (Pb), arsenic (As), manganese (Mn), cadmium (Cd), chromium (Cr), etc., exceed the limits specified in the standards. Relatively speaking, the concentrations of harmful substances in the leachate of the test pieces obtained in Examples 1-3 all meet the requirements of the standards. Therefore, these test pieces will not cause environmental risks to soil and water quality in civil engineering applications.

[0078] 5. According to the specification of "Planting Grass Brick" (NY / T 1253-2006), the present invention has a variety of embodiments that meet the standard. The detailed comparison of the specific performance indicators and specification requirements of these embodiments is shown in Table 11.

[0079] Table 11 Examples and standard requirements of the grass bricks of the present invention

[0080] The value (0.3%) in the table refers to the addition of 0.3% sodium methyl silicate, and (0.5%) refers to the addition of 0.5% sodium methyl silicate.

[0081] The experimental results in Table 11 show that the test pieces with the addition of waterproofing agent have a lower water absorption rate and fully meet the relevant standards. In addition, the antifreeze performance data of the above-mentioned Examples 5, 7-9 are obtained after 30 freeze-thaw cycles. For example, the strength loss of Example 7 after 30 freeze-thaw cycles is 20.9%. It can be observed from the table data that the test pieces made in Examples 5 and 8 at two different waterproofing agent dosages have met the requirements for antifreeze properties in the "Grass Brick" standard.

[0082] In addition, as the number of freeze-thaw cycles increases, the compressive strength shows an accelerated downward trend, so it can be considered that Example 7 (0.5%) and Example 9 (0.5%) also meet the standard of frost resistance. Therefore, the present invention can provide multiple solutions for preparing grass bricks from phosphogypsum-based materials. If the goal is to use as much phosphogypsum as possible to improve its utilization rate, then Example 1 and Example 3 and the preparation process of adding less than 1% waterproofing agent on their respective basis can be selected. The mass proportion of phosphogypsum in Example 1 and Example 3 is as high as 70% and 82% respectively. On the other hand, if there are higher requirements for the strength and durability of grass bricks, Example 2 and the preparation process of adding less than 1% waterproofing agent in Example 2 can be selected.

[0083] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A grass-planting brick based on phosphogypsum-based composite cementitious material, characterized in that: The raw materials include 100 parts by mass of phosphogypsum-based composite cementitious material, 0.05-0.3 parts of retarder, 0-0.5 parts of waterproofing agent, 0-70 parts of aggregate and 40-70 parts of water. The phosphogypsum-based composite cementitious material comprises 70 to 90 parts of modified phosphogypsum powder, 10 to 30 parts of blast furnace slag powder and 0 to 3.5 parts of alkaline activator; the modified phosphogypsum powder is obtained by calcining and ball milling the phosphogypsum powder.

2. The grass-planting brick based on phosphogypsum-based composite cementitious material according to claim 1 is characterized in that: The alkaline activator includes calcium hydroxide.

3. The grass-planting brick based on phosphogypsum-based composite cementitious material according to claim 1, characterized in that: The retarder comprises a vegetable protein retarder; and the waterproofing agent comprises sodium methyl silicate.

4. The grass-planting brick based on phosphogypsum-based composite cementitious material according to claim 1, characterized in that: The aggregate includes coarse aggregate and fine aggregate in a mass ratio of (1.2-1.5):1, the particle size of the coarse aggregate is 4.75-26.5 mm, the particle size of the fine aggregate is below 4.75 mm, and the particle gradation of the coarse aggregate and the fine aggregate is a continuous gradation.

5. The grass-planting brick based on phosphogypsum-based composite cementitious material according to claim 4 is characterized in that: The coarse aggregate is limestone aggregate, and the fine aggregate is river sand; or the coarse aggregate and the fine aggregate are both recycled aggregates, and the recycled aggregate is obtained by mixing modified phosphogypsum powder and water and then granulating.

6. The grass-planting brick based on phosphogypsum-based composite cementitious material according to claim 4, characterized in that: The particle gradation of the coarse aggregate is: 16 mm to 26.5 mm accounts for 30%, and 4.75 mm to 16 mm accounts for 70%; the particle gradation of the fine aggregate meets the continuous gradation of natural sand zone II.

7. The grass-planting brick based on phosphogypsum-based composite cementitious material according to claim 1, characterized in that: The modified phosphogypsum powder has a fineness of 80-200 meshes; the blast furnace slag powder is S95 grade slag.

8. The grass-planting brick based on phosphogypsum-based composite cementitious material according to claim 1, characterized in that: The water-solid ratio is 0.3-0.

4.

9. The method for preparing grass-planting bricks based on phosphogypsum-based composite cementitious materials according to any one of claims 1 to 8, characterized in that: The following steps are involved: The phosphogypsum powder is calcined to obtain calcined phosphogypsum powder, and the calcined phosphogypsum powder is ball-milled to obtain modified phosphogypsum powder; The modified phosphogypsum powder, blast furnace slag powder and alkaline activator are mixed to obtain a phosphogypsum-based composite cementitious material; The phosphogypsum-based composite cementitious material, a retarder, a waterproofing agent, an aggregate and water are mixed to prepare a gypsum mortar; The gypsum mortar is poured into a mold, cured and formed, and a grass-planting brick based on the phosphogypsum-based composite cementitious material is obtained.

10. The method for preparing grass-planting bricks based on phosphogypsum-based composite cementitious materials according to claim 9, characterized in that: The calcination temperature is 200°C to 300°C, and the calcination time is 10 to 20 min; The aggregate is first soaked in water and then mixed.